Immunosuppressive therapy after solid-organ transplantation: does the INTERMED identify patients at risk of poor adherence? - Michaud L; Ludwig G; Berney S; Rodrigues S; Niquille A; Santschi V; Favre AS; Lange AC; Michels AA; Vrijens B; Bugnon O; Pilon N; et al. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Lack of adherence to medication is a trigger of graft rejection in solid-organ transplant (SOT) recipients. Objective: This exploratory study aimed to assess whether a biopsychosocial evaluation using the INTERMED instrument before transplantation could identify SOT recipients at risk of suboptimal post-transplantation adherence to immunosuppressant drugs. We hypothesized that complex patients (INTERMED>20) might have lower medication adherence than noncomplex patients (INTERMED≤20). Methods: Each patient eligible for transplantation at the University Hospital of Lausanne, Switzerland, has to undergo a pre-transplantation psychiatric evaluation. In this context the patient was asked to participate in our study. The INTERMED was completed pre-transplantation, and adherence to immunosuppressive medication was monitored post-transplantation by electronic monitors for 12 months. The main outcome measure was the implementation and persistence to two calcineurin inhibitors, cyclosporine and tacrolimus, according to the dichotomized INTERMED score (>20 or ≤20). Results: Among the 50 SOT recipients who completed the INTERMED, 32 entered the study. The complex (N=11) and noncomplex patients (N=21) were similar in terms of age, sex and transplanted organ. Implementation was 94.2% in noncomplex patients versus 87.8% in complex patients (non-significant p-value). Five patients were lost to follow-up: one was non-persistent, and four refused electronic monitoring. Of the four patients who refused monitoring, two were complex and withdrew early, and two were noncomplex and withdrew later in the study. Conclusion: Patients identified as complex pre-transplant by the INTERMED tended to deviate from their immunosuppressant regimen, but the findings were not statistically significant. Larger studies are needed to evaluate this association further, as well as the appropriateness of using a nonspecific biopsychosocial instrument such as INTERMED in highly morbid patients who have complex social and psychological characteristics.